LITERATURE STUDY: THE SQ4R METHOD IN IMPROVING READING COMPREHENSION IN STUDENTS - Ria Rafianti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lampung, 2025)
This study aims to evaluate the effectiveness of the SQ4R method in improving students' reading comprehension skills, using a literature review approach. The SQ4R method consists of six strategic steps: Survey, Question, Read, Recite, Reflect, and Review. These six stages are designed to foster active engagement of students in the reading process. This study relies on references from various national and international scientific journals, as well as relevant educational books. Based on the literature analysis, it was found that the SQ4R method not only helps students understand the literal content of the text but also strengthens their inferential and critical thinking skills. One of the key aspects of this approach is the Reflect stage, which encourages students to connect the reading material with their previous experiences and knowledge, thereby creating a more meaningful and contextual learning process. In conclusion, the SQ4R method has proven to be effective in strengthening reading comprehension skills and is worthy of being integrated into learning that meets the demands of the 21st-century curriculum. Keywords: SQ4R, reading comprehension, learning strategies, literature studies